EP1188 Topic treatment of vulvar lichen sclerosus: symptoms control and risk of progression to malignancy. (1st November 2019) - Sina, FP; Blangiardo, P; Lamanna, M; Magni, S; Vecchione, F; Chiari, S; Gnecchi, L; Landoni, F; Fruscio, R
Abstract : Introduction/Background: vulvar lichen sclerosus (VLS) is a chronic inflammatory dermatosis usually associated with symptoms that cause significant physical discomfort and emotional distress. The therapy of VLS is controversial, and factors that can influence the progression to neoplastic lesions are not clear. Methodology: this is a retrospective analysis of women with a diagnosis of VLS made between 2005–2010 at San Gerardo Hospital, Monza. Patients were treated with mometasone furoate 0.1% ointment for a 30-days period in association with emollient creams followed by a maintenance phase with emollient creams only at least twice a day. The efficacy of therapy was evaluated in women with at least one follow-up visit; the development of preneoplastic and neoplastic lesions was evaluated only in patients with a follow-up of at least 1 year. The association between clinical data (including demographics and response to therapy) and progression to cancer was evaluated using univariate and multivariate analysis. Results: a total of 251 women were included in this retrospective analysis. Median age at diagnosis was 63 years. The efficacy of therapy was evaluated in 231 patients. Symptoms remission was obtained in 65% of patients, while 16% required topical steroids in addition to emollient creams in the maintenance phase. Therapy was not effective in 19% of patients. Neoplastic progression was evaluated in 144 patients. 28 women developed a vulvar carcinoma (24) or VIN (4) with a median time from VLS diagnosis of 51 months. Patients without symptoms control were significantly more likely to develop a neoplastic lesion during follow up at a multivariate analysis (p: 0.004). Conclusion symptoms remission can be obtained in the majority of patients with VLS using emollient creams only in the maintenance phase. Patients who do not respond to therapy should be carefully monitored, as they have a higher risk of developing neoplastic lesions. Disclosure: Nothing to disclose